Leadership in Action: Leadership Briefing - How Managers View Success: Perspectives of High-Achieving Women - Ruderman, Marian; Ohlott, Patricia; Panzer, Kate; King, Sara (Center for Creative Leadership, 1999)
Many women perceived that their organizations defined success narrowly, focusing on performance and on measurements such as meeting financial or production goals.